DETERMINAN PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP KEMANDIRIAN KEUANGAN DAERAH - Riyans Ardiansyah (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2023)
Original Local Revenue and Intergovernmental Transfer are sources of regional income that are used to finance regional development. These two sources of income are indicators in determining the level of independence of a region from a financial standpoint. This study aims to determine the level of financial independence of a region using Original Local Revenue and Intergovernmental Transfer as measuring tools. The analytical method used is quantitative descriptive analysis with SPSS 25.00. The data used is secondary data in the form of a report on the realization of the revenue and expenditure budget for the city of Tarakan for 10 years, namely from 2013 to 2022. The data comes from the Tarakan city BPS office. The results of the study show that Original Local Revenue makes a positive and significant contribution to Financial Self-Sufficiency of Local Governments, while Intergovernmental Transfer have a negative influence on Financial Self-Sufficiency of Local Governments in the city of Tarakan. Original Local Revenue and Intergovernmental Transfer simultaneously influence to Financial Self-Sufficiency of Local Governments.